Gerald A. ARBUCKLE: Culture, Inculturation, and Theologians. A Postmodern Critique. Foreword by Anthony Gittins, CSSp. Collegeville, Minnesota: A Michael Glazier Book, Liturgical Press, 2010. 200 p. ISBN 789-08146-5458-3. - Peelman, Achiel (Annales Missiologici Posnanienses, 2015)
Recenzja